Correlation between the prevalence of plasmids and AMR genes in the environmental isolates of different bacterial species - Rahman, Wasifa Ar (2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Science in Biotechnology, 2023.